CAREC transport strategy 2030. (Asian Development Bank, 2020)
It separates trade facilitation from transport and links to the overall CAREC 2030 program in the areas of enhanced connectivity and sustainability. This strategy underscores increasing sustainability and network quality alongside continued construction and rehabilitation of transport corridors, and places more emphasis on multimodal connectivity, road asset management, road safety, and performance-based maintenance goals. The CAREC Transport Strategy 2030 will be implemented in conjunction with the CAREC Integrated Trade Agenda 2030.